Menulis Puisi Menggunakan Metode Langsung - Imelda Oliva Wissang; Maria Lito Teluma; Marianus Robertus Bolan Wokal (Departement of Mathematics Education, 2023)
Writing poetry with the direct method is training given to students of SMPK Ratu Damai, sub-district of Waibalun, East Flores district to answer questions related to the implementation of the direct learning model in poetry writing training for class VII students of SMPK Ratu Damai, Waibalun sub-district, East Flores district. The purpose of this training activity is to describe the implementation of the direct learning model in poetry writing training for class VII SMPK Ratu Damai which can provide benefits for students, schools, and teachers. Writing skills can only be implemented through focused and continuous practice. To produce good writing requires continuous process and practice. The method of this training activity is carried out in a direct way which is carried out in stages. The first part begins with an explanation of the material and the second part is an exercise in writing poetry. This training is able to encourage enthusiasm, motivation, interest, and increase students' knowledge about poetry writing techniques with good results. The results of the poetry writing training in class VII SMPK Ratu Damai, Waibalun sub-district, East Flores district showed that students were skilled at writing poetry especially in choosing diction, figurative language, imagery, variety, and good typography.